The revolt of the provinces : anti-Gypsyism and right-wing politics in Hungary - Szombati, Kristóf ([New York] : Berghahn Books, 2018)
"The first in-depth ethnographic monograph on the New Right in Central and Eastern Europe, The Revolt of the Provinces explores the making of right-wing hegemony in Hungary over the last decade. It explains the spread of racist sensibilities in depressed rural areas, shows how activists, intellectuals and politicians took advantage of popular racism to empower right-wing agendas and examines the new ruling party's success in stabilizing an 'illiberal regime'. To illuminate these important dynamics, the author proposes an innovative relational framework, focusing on interaction between social antagonisms emerging on the local level and struggles waged within the political public sphere"--
Historic contextualization : "Gypsies", "Magyars" and the state -- Popular racism in the northeast : the case of Gyongyospata -- Redemptive anti-Gypsyism : the transposition of struggles from the social to the political domain -- Right-wing rivalry and the dual state -- The limits of racist mobilization : the case of Devecser -- From racism to ultranationalism : Jobbik's transformation through ethnographic lens.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Racism -- Hungary; Romanies -- Hungary -- Social conditions; Nationalism -- Hungary; Right-wing extremists -- Hungary; Hungary -- Politics and government -- 21st century; Racisme -- Hongrie; Tsiganes -- Hongrie -- Conditions sociales; Nationalisme -- Hongrie; Extrémistes de droite -- Hongrie; Hongrie -- Politique et gouvernement -- 21e siècle.; HISTORY -- Europe -- Western; HISTORY -- Europe -- Germany; POLITICAL SCIENCE / General; Romanies -- Social conditions; Right-wing extremists; Racism; Nationalism; Conservatism; Democracy; Politics and government; Right and left (Political science); Hungary; 2000-2099; Since 1989